2006
DOI: 10.1093/jmedent/43.6.1215
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of the Malaria Vectorial System in Cameroon: Contribution of Secondary Vectors to Malaria Transmission

Abstract: Malaria transmission in Africa is a dynamic and complex system that is so far superficially understood. Further knowledge is required to improve control of the disease. In the present report, we highlight the contribution of the so-called "secondary" malaria vectors to the overall parasite transmission intensity in several sites across Cameroon, through a retrospective analysis of surveys from the Organisation de Coordination pour la lutte Contre les Endémies en Afrique Centrale database. In total, 48,490 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
116
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 32 publications
6
116
3
1
Order By: Relevance
“…nili and An. moucheti ) have been described [10] with nine secondary vectors of local importance ( An. paludis , An.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…nili and An. moucheti ) have been described [10] with nine secondary vectors of local importance ( An. paludis , An.…”
Section: Discussionmentioning
confidence: 99%
“…nili (Theobald, 1904) and An. moucheti Evans, 1925 are classified as major vectors [10]. The other species amongst which are An.…”
Section: Introductionmentioning
confidence: 99%
“…[8]. However, as studies of malaria transmission have identified the presence of more than one significant malaria vector within some regions [37], [38] there is again reason to doubt the validity of this assumption in many contexts.…”
Section: Methodsmentioning
confidence: 99%
“…Rota is in a rural setting, on the marshes of Lake Victoria in Western Kenya, with a tropical climate and annual rainfall Ͼ1,000 mm. In all three highly endemic malaria localities, transmission is perennial, with inoculation rates of Ϸ200 (Tibati), Ϸ300 (Simbock), and 100-300 (Rota) infective bites per human per year (2,3,37). keys (6, 7), the mosquitoes were dissected in a saline solution on the morning of their collection in Cameroon and 1 week after collection in Rota to allow for the development of oocysts in infected females.…”
Section: Methodsmentioning
confidence: 99%
“…Prevention and cure of the disease are major publichealth challenges that are tackled by using several strategies, among them vector control. The transmission of Plasmodium falciparum, the agent of malignant malaria, involves a complex vectorial system consisting of Ϸ10 Anopheles species, colonizing different ecoclimatic settings, regions, and seasons in strongly variable relative abundances (2)(3)(4)(5).…”
mentioning
confidence: 99%